An experimental study on hybrid fiber reinforced concrete beams subjected to torsion. (2021) - Saravanakumar, P; Sivakamidevi, M; Meena, K; Yamini, S.P
Abstract: Experimental investigations were carried out to study the mechanical performance and torsional behaviour of hybrid fiber reinforced concrete beams. Steel fibers and Glass fibers were used with varying fiber content such as 0% 0.5% 1.0% and 1.5% by volume of concrete to cast the specimens for this study. The experimental study results confirmed that the mechanical performance of the concrete was remarkably improved with the addition of hybrid fibers upto 1% by volume of concrete. The torsional strength in the cracking state and post cracking state was improved in hybrid fiber reinforced concrete and this depends on the volume of fiber content in concrete.